Inhibitory effect of Astragalus polysaccharide on osteoporosis in ovariectomized rats by regulating FoxO3a /Wnt signaling pathway - Ou,Li (2019)
Abstract Purpose: To investigate inhibitory effect of Astragalus polysaccharide (APS) on osteoporosis in ovariectomized rats by regulating FoxO3a/Wnt2 signaling pathway. Methods: Postmenopausal osteoporosis (PMOP) animal model was developed by excising the bilateral ovaries of rats. The model rats were administered with APS (200 mg/kg, 400 mg/kg, 800 mg/kg) by intragastric administration once daily for 12 weeks. Bone density, bone metabolism index and oxidative stress index were measured in all groups. Furthermore, the regulation of APS of FoxO3a / Wnt2 signaling pathway was observed. Results: APS has an estrogen-like effect, which can increase bone mass, lower serum ALP and BGP values, increase blood calcium content, and increase bone density of the femur and vertebrae in rats. At the same time, APS can increase the bone mineral content of the femur, increase the maximum stress, maximum load and elastic modulus of the ovariectomized rats, improve oxidative stress in rats by increasing the gene expression of β-catenin and Wnt2 mRNA and inhibiting the gene expression of FoxO3a mRNA. Conclusion: Astragalus polysaccharide can effectively alleviate oxidative stress-mediated osteoporosis in ovariectomized rats, which may be related to its regulation of FoxO3a/Wnt2/β-catenin pathway.